Analysis of the utilization of zakat, infaq, and alms during the Covid-19 pandemic: CIBEEST model approach - Muhammad Farhan Razzack; Purbayu Budi Santosa; Mochammad Ardani; Annisa Maulidia Alfian (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – One of the instruments in Islamic economics that can help alleviate poverty during Covid-19 is zakat, infaq, and alms. This study aims to analyze the effect of ZIS utilization by the Jogokariyan Mosque in reducing the poverty of its congregation.Methodology – The approach is quantitative with CIBEST analysis techniques and different tests (Paired T-test and Mann-Whitney test). Data were collected through interviews with the Jogokariyan Mosque administrators and distributing questionnaires to 33 congregations that received ZIS benefits as a population. Findings – The results of the analysis of the CIBEST model show that the use of ZIS can reduce the material and spiritual poor of the congregations who receive ZIS assistance. The results of the Paired T-test and the Mann-Whitney test showed that all variables experienced positive differences before and after receiving ZIS assistance from the Jogokariyan Mosque.Implications – Community empowerment through ZIS funds from the Jogokariyan Mosque can be further improved, particularly by increasing the number of beneficiaries (mustahik). The practice applied by the Jogokariyan Mosque can also be imitated by other mosques so that they can become an instrument of economic recovery during the Covid-19 period. Originality – This study looks at how the empowerment of Islamic social funds is carried out through mosques. This shows that the mosque's function is not only a place of worship but also an important role in the community's social conditions.